Numerical Modeling of Soil-Pile-Interaction with Near and Far Field Earthquake's Effects - Mohammad Shahmohammadi Mehrjerdi; Ahmad Ali Fallah; S.T. Tabatabaei Aghda (Salehan Institute of Higher Education, 2017)
This paper studies Near and Far Field effects of the response of a column-pile to earthquakes considering Dynamic-Soil-Structure-Interaction (DSSI) effects in soft clay (Vs<180 m/s ) and stiff clay (180<Vs<375 m/s). Opensees software that can simulate the dynamic time history analysis is used. Both kinematic and inertial interactions are considered and Finite Element Method (FEM) is used to solve DSSI. The direct method applies to 3D modeling of the layered soil and column-pile. A Pressure Independ Multi Yield Surface Plasticity Model is used to simulate different kinds of clay behavior. Time history seismic analyses provide for the mass and stiffness matrices to evaluate dynamic structural response with and without directivity effects for Near and Far Field earthquakes. Results show that the Multi-Yield-Surface-Kinematic-Plasticity-Model can be used instead of bilinear springs between piles and clay soil, for both Near Field and Far Field earthquakes. In addition, comparing Near and Far Field analyses, acceleration response spectrum at the top of the structure in the Far Field increases with the softness of the soil more than that in the Near field.